2014
DOI: 10.1007/s11033-014-3195-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Xmn1 −158 γG variant with severity and HbF levels in β-thalassemia major and sickle cell anaemia

Abstract: Haemoglobinopathies including β-thalassemia and sickle cell anaemia (SCA) are considered to be classical monogenic diseases. There is considerable clinical variability between patients inheriting identical β-globin mutations. The reasons for this variability are not well understood. Previous studies have suggested that a variety of genetic determents influence different clinical phenotypes. The genetic variants that modulate HbF levels have a very strong impact on ameliorating the clinical phenotype. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…These findings could be explained by the inhibitory effect of HbF on deoxy‐HbS polymerization (which in turn is the major driver of the pathophysiology of this disease) . These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies . Moreover, Sheehan et al demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These findings could be explained by the inhibitory effect of HbF on deoxy‐HbS polymerization (which in turn is the major driver of the pathophysiology of this disease) . These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies . Moreover, Sheehan et al demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers.…”
Section: Discussionsupporting
confidence: 69%
“…35 These observations were to a great extent similar to those reported in Indian SCD patients, where it was found that carriers of the minor allele of rs7482144 had a milder disease with higher hemoglobin and HbF, and lower transfusion and pain crises frequencies. 36,37 Moreover, Sheehan et al 38 demonstrated that minor alleles at rs1427407 were associated with higher Hb and lower pain frequencies compared to noncarriers. While Lettre et al 15 failed to find a significant association between pain episodes frequencies and individual SNP that they studied (including rs7482144 and rs9399137), they did find an inverse correlation between HbF and pain frequency.…”
Section: Americans and Is Intermediate Between The Lower Rates Repormentioning
confidence: 99%
“…A significant difference in the high and low percentage of HbF in CC, CT, and TT bearing individuals (P<0.01) were observed. This study confirms that increased γG-globin expression, associated with the Xmn1 polymorphism ameliorates the clinical severity in β-thalassemia as well as SCA in the study population [32].…”
Section: • Xmn-1 (Xanthomonas Maniholis-1) Restriction Sitesupporting
confidence: 85%
“…It has been reported that Gγ-polymorphism increases the production of Hb-F, reducing the severity of the disease. 15,[21][22][23] Thus envisage that presentation of HbS with the support of Xmn-I polymorphism presents in thalassemia intermedia phenotype.…”
Section: Discussionmentioning
confidence: 99%